(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
As factors directly related to the costs of drilling, time and operational efficiency are of major significance in the drilling operations. One of the criteria in the operational efficiency of drilling is the rate of penetration of the drilling bit. Numerous factors affect the rate of penetration. Identification of the effective factors on rate of penetration may lead to a more accurate assessment of drilling time and as a result the controlling of operational costs. The concurrent effect of the entire influential factors as well as the differing significance of each of them on the rate of penetration makes the study and optimization of drilling operations much more complicated and difficult. Using the rock engineering systems (RES), the impact of effective operational and environmental factors on the rate of penetration has been assessed in this article and a model has been proposed for prediction of the rate of penetration. Data from one of the wells within Azadegan oilfield have been used in order to study the impact of effective factors on the rate of penetration. To this end, the effective factors on rate of penetration are initially identified and then an index called “the penetration index” is proposed through application of the rock engineering systems approach. This index has been calculated at four different depths along the aforesaid well. The results suggested the compliance of penetration rate predictions with field observations. Moreover, porosity and uniaxial compressive strength are the most effective factors on the rate of penetration whereas the unit weight of drilling fluid has the least impact.